2003
DOI: 10.1108/09564230310474183
|View full text |Cite
|
Sign up to set email alerts
|

The role of quality practices in service organizations

Abstract: The widespread interest in using quality management to improve organizational performance started in the manufacturing sector and later spread to service organizations. Quality management can be viewed as an approach to management characterized by its principles, practices and techniques (Dean and Bowen, 1994). Each principle is implemented through a set of practices, which consist of activities such as collecting customer information, improving work processes and managing employees. The practices are, in turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 25 publications
4
66
0
7
Order By: Relevance
“…For example, Terziovski and Samson's (1999) analysis was supportive, since size moderated the association between QM and performance, in particular, defect rates and warranty costs. When focusing on specific QM dimensions, Gustafsson et al (2003) found that some practices related to process orientation directly impact customer satisfaction in large organizations, but this effect was not evident in smaller organizations. Hendricks and Singhal (2001), however, concluded that smaller firms can benefit more from QM.…”
Section: Contingency Analysis Of the Efqm Criteriamentioning
confidence: 98%
“…For example, Terziovski and Samson's (1999) analysis was supportive, since size moderated the association between QM and performance, in particular, defect rates and warranty costs. When focusing on specific QM dimensions, Gustafsson et al (2003) found that some practices related to process orientation directly impact customer satisfaction in large organizations, but this effect was not evident in smaller organizations. Hendricks and Singhal (2001), however, concluded that smaller firms can benefit more from QM.…”
Section: Contingency Analysis Of the Efqm Criteriamentioning
confidence: 98%
“…In its second wave, it was labelled total quality management (TQM), while today it is often referred to as Six Sigma or lean production. These quality initiatives have been used to improve organisational performance, firstly on the manufacturing floor, and later in all parts of the organisation, not only in manufacturing firms but also in service firms (Gustafsson, Nilsson, & Johnson, 2003;Lam, Lee, Ooi, & Lin, 2011;Talib, Rahman, & Qureshi, 2011). Although new services launched continually to satisfy existing and future customer needs, customer satisfaction with services does not reach the same levels as it does for products (Fornell, Johnson, Anderson, Cha, & Everitt Bryant, 1996;.…”
Section: Introductionmentioning
confidence: 99%
“…The first sphere is related to the use of internal activities in the provider's sphere that influence the improvement of the customer's service perception (e.g., Calabrese 2012; Edvardsson, Larsson, and Setterlind 1997;Gustafsson, Nilsson, and Johnson 2003). These internal activities can be regarded as prerequisites for the coherence of the service outcome with customer expectations (Edvardsson and Olsson 1996), which in turn influences customer satisfaction and business performance (Gustafsson, Nilsson, and Johnson 2003). The second sphere is the sphere of interaction that takes place during the moment of exchange (e.g., Crane and Clarke 1988;Wu et al 2015).…”
Section: Service Qualitymentioning
confidence: 99%
“…(Dean and Bowen 1994, p. 395) In a business context, the role of quality management has been debated extensively. Many studies have tested the relationship between implementing quality management and firm performance (e.g., Anderson, Fornell, and Lehmann 1994;Baird, Hu, and Reeve 2011;Gustafsson, Nilsson, and Johnson 2003;Lemak, Reed, and Satish 1997;Nilsson, Johnson, and Gustafsson 2001;O'Neill, Sohal, and Teng 2016). Although the results are contradictory, most studies show a positive relation between quality management and the performance of a firm.…”
Section: Interventions and Principlesmentioning
confidence: 99%